Chronic Hemodialysis in Small Children. Issue 3 (June 2016) - Novljan, Gregor; Rus, Rina R; Premru, Vladimir; Ponikvar, Rafael; Battelino, Nina
Abstract: When peritoneal dialysis is inapplicable, chronic hemodialysis (HD) becomes the only available treatment option in small children. Due to small patient size, central venous catheters (CVC) are mainly used for vascular access. Over the past 4 years, four children weighing less than 15 kg received chronic HD in our unit. A total of 848 dialysis sessions were performed. Altogether, 21 catheters were inserted. In all but one occasion, uncuffed catheters were used. Catheter revision was performed 15 times during the study period, either due to infection or catheter malfunction. The median number of catheter revisions and the median line survival was 3.0/patient‐year and 53 days (range; 6–373 days), respectively. There were 14 episodes of catheter related infections requiring 11 CVC revisions (78.6%). The median rate of line infections was 2.8/patient‐year. Chronic HD in small children is demanding and labor intensive. Issues pertain mainly to CVCs and limit its long‐term use.